Advancing bat monitoring: Assessing the impact of unmanned aerial systems on bat activity. - Marc Roswag; Anna Roswag; Matthias Sebastian Roswag; Joanna Fietz; Tessa Touridocht Taefi (PLoS ONE)
With the increasing height and rotor diameter of wind turbines, bat activity monitoring within the risk area becomes more challenging. This study investigates the impact of Unmanned Aerial Systems (UAS) on bat activity and explores acoustic bat detection via UAS as a new data collection method in the vicinity of wind turbines. We tested two types of UAS, a multicopter and a Lighter Than Air (LTA) UAS, to understand how they may affect acoustically recorded and analyzed bat activity level for three echolocation groups: Pipistrelloid, Myotini, and Nyctaloid. We hypothesized (i) that the LTA UAS will not affect bat activity levels while a multicopter, due to higher noise emission, might have a negative impact. Our results support this hypothesis, because multicopter flights have a highly significant negative impact on bat activity levels with a medium effect size, particularly for the Myotini (P < 0.001, dm = 0.54) and Nyctaloid group (P < 0.001, dn = 0.55) and a small effect size for the Pipistrelloid group (P < 0.001, dp = 0.36). In contrast, the LTA UAS had no significant effect on bat activity for each echolocation group (P > 0.05 for each group), suggesting its suitability for non-intrusive acoustic monitoring. Furthermore, we hypothesized (ii) that larger UAS propellers prevent the deterrent effect on bats. However, despite the use of larger propellers for the multicopter UAS compared to previous studies, we observed a deterrence effect for all echolocation groups. Additionally, we hypothesized that (iii) any initial deterrence or attraction effect might decrease over time. Our results did not support this hypothesis because we did not observe any habituation of bats to UAS within the 15-minute flight period. Our study highlights the potential of UAS for bat monitoring but underscores the critical importance of selecting appropriate UAS types and operating noise levels for successful surveillance efforts.